Implementation of Waste Reduction Policy Based on Regional Regulation Number 13 of 2019 concerning Amendments to Regional Regulation Number 3 of 2013 concerning Waste Management in South Tangerang City - Oktavia, Fiona; Salam, Rahmat (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2025)
This study analyzes the implementation of Tangerang Selatan’s waste reduction policy, as outlined in Regional Regulation No. 13/2019, using Merilee S. Grindle’s policy implementation framework. Methodology applied on this research is qualitative methodology using interview, surveys, and observation. The findings indicate that while several programs, such as Zero-Waste Homes, TPS 3R, and Intermediate Treatment Facilities (ITF), have been successfully implemented, the overall policy effectiveness remains suboptimal. Key challenges include limited human resources, ineffective public communication, and the absence of a structured incentive- and penalty-based compliance system. The persistence of illegal waste dumping and low participation in waste sorting at the household level further hinder progress. Despite these obstacles, various supporting factors contribute to the policy’s implementation, including public awareness campaigns, private sector collaboration, and the integration of waste management technology. To enhance policy effectiveness, this study proposes several recommendations: strengthening collaboration with the private sector through CSR programs, implementing Extended Producer Responsibility (EPR) for upstream waste reduction, improving human resource capacity through training, utilizing social marketing for better public communication, integrating technology in waste processing, and establishing a structured compliance monitoring system. These measures are essential to achieving Tangerang Selatan’s waste reduction targets and ensuring long-term sustainability in waste management.